Administrative Burdens at the Department of Industry and Trade, Central Java Province, Indonesia - Lubna Firdausa H; Puspa W, Harumsari; Tiara Aurora Alia S (Arkus, 2024)
The objective of this article is to elucidate the administrative onus within the Department of Industry and Trade in the Central Java Province. Various perspectives, including expert analyses and interviews with sources, might be employed to elucidate this issue. This research employed methodological strategies such as informant interviews, historical reviews, and evaluations grounded in specific facts. This paper employs a normative legal methodology, utilizing primary data sources such as interviews and secondary data sources such as literature reviews, including legal and non-legal materials. Based on this analysis, it can be deduced that there exists a theory regarding administrative burden, specifically the concept of compliance burden. The government's policies have consequential effects on the community. There are signs of bureaucratic obstacles inside the Industry and Trade Department of the Central Java Province.